The Contested Grounds of Democracy's Noninstrumental Value: Deliberative Democracy Versus Public Equality - Vittorio Gerosa (Constellations, 2026)
ABSTRACT Disagreement about democracy's noninstrumental value often sees the opposition between two competing approaches. Liberty‐based arguments assign normative priority to a principle of liberty, thereby focusing on democratic self‐government as the core principle through which political authority can be reconciled with individual liberty. Equality‐based arguments fundamentally appeal to equality instead, thus commending democratic procedures for treating citizens as equals in the decision‐making process. This paper targets Thomas Christiano's public equality argument for democracy, showing that its tacit reliance on a noncomparative norm of respect for the free and autonomous person leads it back to the liberty framework, as traditionally understood.